Improvement of the Distribution Systems Resilience via Operational Resources and Demand Response - Home-Ortiz, Juan M.; Melgar-Dominguez, Ozy D.; Javadi, Mohammad S.; Mantovani, Jose Roberto Sanches; Catalao, Joao P. S. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This work presents a restoration approach for improving the resilience of electric distribution systems (EDSs) by taking advantage of several operational resources. In the proposed approach, the restoration process combines dynamic network reconfiguration, islanding operation of dispatchable distributed generation (DG) units, and the pre-positioning and displacement of mobile emergency generation (MEG) units. The benefit of exploring a demand response (DR) program to improve the recoverability of the system is also taken into account. The proposed approach aims to separate the in-service and out-of-service parts of the system while maintaining the radiality of the grid. To assist the distribution system planner, the problem is formulated as a stochastic scenario-based mixed-integer linear programming model, where uncertainties associated with PV-based generation and demand are captured. The objective function of the problem minimizes the amount of energy load shedding after a fault event, as well as PV-based generating curtailment. To validate the proposed approach, adapted 33-bus and 83-bus EDSs are analyzed under different test conditions. Numerical results demonstrate the benefits of coordinating the dynamic network reconfiguration, the pre-positioning and displacement of MEG units, and a DR program to improve the restoration process.
Keywords: Demand response; dynamic reconfiguration; Faces; Indexes; islanding DG operation; Microgrids; mobile emergency generators; resilience; Resilience; restoration; Uncertainty; Voltage